MEDIASI DALAM KASUS PERCERAIAN AKIBAT KEKERASAN DALAM RUMAH TANGGA (KDRT) - Ragil Adi Nugroho; Ananda Megha Wiedhar Saputri; Muhammad Fauzan Hidayat (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2025)
Domestic Violence (DV) is a major cause of divorce in Indonesia. Although the law stipulates mediation as the initial step in the divorce process, its effectiveness in the context of domestic violence remains questionable. This study aims to examine in-depth the process and obstacles to mediation in divorce cases due to domestic violence at the Boyolali Regency Religious Court. The research method used is empirical juridical with a qualitative descriptive approach, through observation, interviews, and literature review. The results indicate that despite clear procedural stages and the involvement of mediators in facilitating communication, the success rate of mediation in domestic violence cases remains low. This is due to regulatory factors, victim trauma, the absence of parties, third-party intervention, and limited mediator resources. Mediation in domestic violence cases remains a complex challenge that requires a specialized approach.